Perbandingan Model Therapeutic Community (TC) dan Narcotics Anonymous (NA) di Pelayanan Kesejahteraan Sosial Adiksi Narkoba - Ritonga, Fajar Utama; Arifin, Adil (JPPUMA Jurnal Ilmu Pemerintahan dan Sosial Politik Universitas Medan Area, 2019)
This study compares the Therapeutic Community model with the Narcotics Anonymous Model which is applied to the Narkotika, Psikotropika dan Obat Terlarang (Narkoba) institutions in increasing resident participation. The research approach used is qualitative with descriptive type. The location of the study was conducted at the Charitas PSE Institution in Deliserdang Regency, Medan Mitra Masyarakat Foundation, which used the Narcotics Anonymous Model. The Narcotics Rehabilitation Institution uses the Therapeutic Community Model, namely: Panti Sosial Permadi Putra (PSPP) Initiated by Deliserdang District, Yayasan Nazar Medan City, LOKA BNN Deliserdang. The population in this study is the entire resident who is in the Rehabilitation Institution which is the location of the study as many as 114 people, the sample of this study is the entire study population with the formula n = N, the sample of this study amounted to 114 people. Techniques for collecting data through literature studies, interview and questionnaires, and field observations. The results showed that from the 7 stages of the participation model used there were differences in the Functional Participation stage using the Therapuetic Community Model (TC) 55.5 "%, while the Narcotic Anonymous (NA) Model was 100%, at this stage the difference was very significant at 44.5 %, and interactive participation using Therapeutic Community Model (TC) 65.4%, while Narcotic Anonymous Model (NA) is 44%, at this stage there is a difference of 21.5%